Hydrogen production via natural gas reforming: A comparative study between DRM, SRM and BRM techniques - Yusuf, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
The world population is escalating at a tremendous scale, and hence the global energy demands. The utilization of fossil fuels on a massive scale is not environmentally friendly and posing threats to global warming. CH4 and CO2 are the two major greenhouse gases (GHGs) that are mainly responsible for the greenhouse effect. Gas reforming techniques are promising alternatives to utilize the two GHGs and produce alternative sources of fuel such as syngas and hydrogen. Steam, dry and bireforming of methane are the three main gas reforming processes that can be used for hydrogen and syngas production. These gas reforming reactions are highly endothermic in nature; hence catalyst development is another aspect that is still persistent. The SRM reaction is an extensively used and accepted method for hydrogen production due to its comparatively lower activation energy requirement than BRM and DRM. However, DRM can be a promising technique to produce syngas, since the syngas produces is with H2: CO of unity. The syngas produced by DRM can be used directly in Fischer-Tropsch synthesis to produce higher hydrocarbons. Â© 2021 IEEE.